2017
DOI: 10.1158/0008-5472.can-16-2982
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SRC Coactivators Blocks the Tumor-Initiating Capacity of Cancer Stem-like Cells

Abstract: Tumor initiating cells (TICs) represent cancer stem-like cell (CSC) subpopulations within tumors that are thought to give rise to recurrent cancer after therapy. Identifying key regulators of TIC/CSC maintenance is essential for the development of therapeutics designed to limit recurrence. The steroid receptor coactivator 3 (SRC-3) is overexpressed in a wide range of cancers, driving tumor initiation, cell proliferation, and metastasis. Here we report that SRC-3 supports the TIC/CSC state and induces an epithe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 48 publications
1
45
0
Order By: Relevance
“…Consequently, SRC-3 regulates multiple physiological and pathophysiologic actions. 40,41 Our study demonstrated that SRC-3 deficiency impaired IGF-1 signaling from several aspects, thereby affecting platelet production induced by IGF-1. Moreover, the expression of IGF-binding protein 3 is also downregulated when SRC-3 is abolished, resulting in decreased serum IGF-1.…”
Section: Discussionmentioning
confidence: 74%
“…Consequently, SRC-3 regulates multiple physiological and pathophysiologic actions. 40,41 Our study demonstrated that SRC-3 deficiency impaired IGF-1 signaling from several aspects, thereby affecting platelet production induced by IGF-1. Moreover, the expression of IGF-binding protein 3 is also downregulated when SRC-3 is abolished, resulting in decreased serum IGF-1.…”
Section: Discussionmentioning
confidence: 74%
“…21,22 More recently, SRC-3 was reported to be critical for the maintenance of cancer stemlike cells by promoting the expressions of epithelial-to-mesenchymal transition regulators and stem cell markers. 23 However, the distinct role of SRC-3 in the regulation of HSC maintenance and function remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of SRC-3 Ser857 promotes SRC-3 association with transcription factor ATF4 to mediate non-oxidative pentose phosphate pathway and purine synthesis. This study (35) did not evaluate SRC-3 in the context of CSCs, although SRC-3 has been linked to CSC activity (10,11). ATF4 pathway activation was identified by IPA in our studies (Figure 1) and could explain the correlation between PFKFB4 and PELP1/SRC-3driven CSCs.…”
Section: Discussionmentioning
confidence: 73%
“…xenograft models (10). Our laboratory reported that cytoplasmic complexes composed of PELP1 and SRC-3 mediate breast CSC expansion (11).…”
Section: Introductionmentioning
confidence: 99%